Nondestructive testing of rails using nonlinear Rayleigh waves - Masurkar, Faeez (2022)
The present research focuses on evaluating the dislocation-induced material nonlinearity in rails caused by falling of parapets or large rocks during an earthquake or land-slide and consequently appraising their health status using an amplitude-based nonlinear parameter based on Rayleigh wave propagation. The falling of parapets or large rocks onto the rail is simulated through a laboratory experiment. Several cases are considered here with impacts of varying intensities to demonstrate the capability of the nonlinear parameter in diagnosing such damages in the rails. It is found that for a pristine specimen, the first peak of the amplitude-based nonlinear parameter matches well with the physics-based nonlinear parameter, whereas there is a considerable deviation between the two for the specimen with impact damage. Moreover, the linear ultrasonic parameter is also evaluated for different states of damage for studying its effectiveness in diagnosing impact damages in rails. The results reveal that the nonlinear ultrasonic-based method proposed here is very sensitive and helps characterize the health status of the rails in a baseline-free manner.